Corona Lockdown to Locked in Syndrome: A Neurosurgeon’s Perspective - Kalra, Samir K.; Kalra, Vandana; Kumar, Raj (Indian Journal of Neurosurgery, 2020)
We are spending our days today in a nationwide lockdown. The government should be lauded for taking a firm stand and announcing this lockdown well in time. Perhaps the benefits of social distancing cannot be more emphasized to prevent the spread of the dreaded coronavirus as witnessed by some of the developed nations who missed out by announcing it very late. In this lockdown period when we are primarily confined to our home, people face this dilemma of what to do and what lies ahead. Suddenly people find themselves in a situation where they are forced to stay at home and there is fear and turmoil all around. The mindset in this situation quickly becomes negative and as is well known “empty mind is devil’s workshop.” The need of the hour is to get constructively active and keep the positive vibes going.
Keywords: COVID-19; lockdown; locked in syndrome